Idiopathic scoliosis: evaluation of loss of correction in postoperative follow-up - Liliane Faria Garcia; Rodrigo Perroni Cruzeiro; Sávio Loureiro Laborne de Mendonça; Enguer Beraldo Garcia; Roberto Garcia Gonçalves; Sebastião Vasconcelos de Souza; Enguer Beraldo Garcia Júnior (Coluna/Columna, 2014)
OBJECTIVE: To evaluate the postoperative loss of scoliosis correction using third-generation instrumental, comparing the immediately postoperative period, and the last visit of the patients operated on from 2002 to 2010. METHOD: This was a cross-sectional study, conducted by analysis of medical records, in which 45 patients undergoing scoliosis correction were included. Variables were evaluated preoperatively, immediately postoperatively and in the last follow-up visit after surgery. Statistical analysis of data was performed in PASW program, with a significance level of 95%. RESULTS: Among the 45 patients studied, 88.9% were female and 82.8% were in the skeletally immature group. The mean pre-operative Cobb was 57°, the postoperative was 6.5° and at the last visit, it was 7.04°. There was no statistic difference between postoperative Cobb angle and that at the last examination (p = 0.176). CONCLUSION: There was no significant loss of scoliosis correction loss between the immediate postoperative and the final radiographic evaluation.